Insights on the interaction of serpentine channels and gas diffusion layer in an operating polymer electrolyte fuel cell: Numerical modeling across scales. (December 2021) - Khatoonabadi, Meysam; Safi, Mohammad Amin; Prasianakis, Nikolaos I.; Roth, Jörg; Mantzaras, John; Kirov, Nikolay; Büchi, Felix N.
Highlights: 3D Lattice Boltzmann simulation of the flow on the cathode side of a micro PEFC at wet and dry operating conditions. 3D X-ray tomographic assessment of serpentine channel geometry and porous structure of GDL. A dry GDL leads to higher magnitude cross-flows under the ribs, transferring gas from one straight channel to the next. The normalized local accumulated cross-flows along the channel are substantially higher in the wet GDL compared to the dry GDL. In electrochemically operating cells, the GDL under the rib will receive more O2 by convection, increasing the local reaction. Abstract: Three-dimensional direct numerical simulations were performed for investigating the flow in a serpentine channel and the under-laying porous gas diffusion layer (GDL) of a micro polymer electrolyte fuel cell (PEFC). The flow field comprised three straight sections and two U-turns. The geometry was acquired with high-resolution (2.9 μm) in situ X-ray tomographic measurements on an operating cell. Simulations considered the GDL under dry and partially saturated conditions, whereby saturation was established via electrochemically produced water. A lattice Boltzmann (LB) methodology was adopted for simulating the single-phase (gas) transport in the actual 3D channel and porous GDL geometry. The global pressure drop in the dry GDL was dominated by the turns in the gas channel, while the pressure drops were quite small along the straight channel sections. In the wet GDL case, however, the pressure drop was mainly dictated by the neck-shaped passages created by the large water clusters inside the channel. Owing to the water blockage, the local accumulated cross-flows along the serpentine channel length, when normalized by the inlet channel flow, were substantially higher in the wet GDL, reaching local values up to 45% compared to 18% for the dry GDL. The implications are that in an electrochemically operating cell, the GDL under the rib would receive more gas (and thus O2 ). The creation of cross-flows through the porous GDL would enhance cell performance under the ribs since diffusion will not be the main driving mechanism for oxygen transport and water evaporation. The analysis indicated that the flow field, although designed as serpentine, behaved like half-interdigitated (with a rib of 1.5 mm, half-serpentine flow field, depending on the state of channel flooding).